Analyzing the Perception of Generation Z in North Sulawesi Towards China’s Belt Road Initiative (Journal of Business and Management, 2022)
The Belt and Road Initiative is a project founded by Chinese President Xi Jinping in 2013. The Belt and Road Initiative is a mega project that is being run by China together with its participating countries, one of which is Indonesia. The Belt and Road Initiative provides infrastructure investment for participating countries. This can be categorized as an opportunity and brings good optimism to participants because it can encourage economic growth. However, it turns out that there are several factors that cause differences in perceptions, possibilities of success, and opportunities from BRI. This study aims to determine the perception of Generation Z in North Sulawesi towards Belt Road Initiatives. The study was conducted using quantitative research where data were collected through online questionnaire distribution in North Sulawesi and analyzed using exploratory factor analysis. The results showed that there were differences in perceptions of BRI, namely positive (Optimism) and negative (Anxiety). There are 6 factors that have been successfully generated. The findings of this study are expected to increase the knowledge of both BRI and participating countries to maximize benefits.Keywords: Anxiety, Belt Road Initiatives, Optimism, Perception